Estudo do precondicionamento para o ensaio de carbonatação acelerada do concreto - Jungblut, Mônica Engel (2019)
Durability indicators are indispensable parameters for assessing and predicting the durability of the element and structure as a whole and must be easily quantifiable by laboratory testing. However, in Brazil there is not yet a standard to standardize the accelerated carbonation test and, therefore, the tests are performed based on international standards or literature data. The accelerated carbonation test is used to obtain the durability indicator for carbonation. One of the important steps for the accelerated carbonation test is preconditioning, which must occur after curing and prior to the onset of accelerated carbonation and aims to achieve an appropriate degree of saturation of the specimen so that the carbonation reactions can occur accelerated form. Due to the lack of standardization and the variety of methodologies found in the literature to perform this step, it was proposed to study the influence of different preconditioning methods on the carbonation results with a view to proposing a methodology. For this, four types of concrete were molded: three of them being without mineral addition, with water/binder of 0,40; 0,55 and 0,70; and onde concrete with replacement of 10% by weight of cement with metakaolin with 0,55 water/binder. The concretes were preconditioned by four different methods, following the recommendations of the ISO 1920-12 (2015), NF EN 13295 (2004), XP P 18-458 (2008) e RILEM TC 116-PDC (1999). Subsequently, the accelerated carbonation test was performed with 3% of CO2, 22°C and 65% of relative humidity. The results showed that the preconditioning type had a significant influence on the carbonation depths, and for the methods of ISO 1920-12 (2015) and NF EN 13295 (2004) the measured depths were smaller, while for the methods according to XP P 18-458 (2008) and RILEM TC 116- PDC (1999) were higher, considering the same type of concrete. In addition, it was observed that concretes with lower carbonation depths presented higher surface humidity at the beginning of the test, and this humidity was reduced at the end of the test, indicating that, for these concretes, the balance between internal humidity and ambient humidity had not yet been established during preconditioning ; this had a significant influence on the carbonation depth results. Thus, the simplest preconditioning method with the least influence of internal humidity in the accelerated carbonation test was XP P 18-458 (2008).